Drug‐resistance development differs between HIV‐1‐infected patients failing first‐line antiretroviral therapy containing nonnucleoside reverse transcriptase inhibitors with and without thymidine analogues1. Issue 9 (13th May 2013) - Santoro, MM; Sabin, C; Forbici, F; Bansi, L; Dunn, D; Fearnhill, E; Boumis, E; Nicastri, E; Antinori, A; Palamara, G; Callegaro, A; Francisci, D; et al.
<x xml:space="preserve">Abstract</x> Objectives We evaluated the emergence of drug resistance in patients failing first‐line regimens containing one nonnucleoside reverse transcriptase inhibitor (NNRTI) administered with zidovudine (ZDV) + lamivudine (the ZDV group) or non‐thymidine analogues (non‐TAs) (tenofovir or abacavir, + lamivudine or emtricitabine; the non‐TA group). Methods Three hundred HIV‐1‐infected patients failing a first‐line NNRTI‐containing regimen (nevirapine, n = 148; efavirenz, n = 152) were included in the analysis. Virological failure was defined as viraemia ≥ 400 HIV‐1 RNA copies/mL for the first time at least 6 months after starting the NNRTI‐based regimen. For each patient, a genotypic resistance test at failure was available. The presence of drug‐resistance mutations in HIV‐1 reverse transcriptase was evaluated by comparing patients treated with NNRTI + zidovudine + lamivudine vs. those treated with NNRTI + non‐TA. Results A total of 208 patients were failing with NNRTI + zidovudine + lamivudine and 92 with NNRTI + non‐TA. No significant differences were observed between the non‐TA group and the ZDV group regarding the time of virological failure [median (interquartile range): 12 (8–25) vs. 13 (9–32) months, respectively; P = 0.119] and viraemia [median (interquartile range): 4.0 (3.2–4.9) vs. 4.0 (3.3–4.7) log10 copies/mL, respectively; P = 0.894]. Resistance to reverse transcriptase inhibitors (RTIs) occurred at a significant lower frequency in the non‐TA group than in the ZDV group (54.3 vs. 75.5%, respectively; P = 0.001). This difference was mainly attributable to a significantly lower prevalence of NNRTI resistance (54.3 vs. 74.0%, respectively; P = 0.002) and of the nucleoside reverse transcriptase inhibitor (NRTI) mutation M184V (23.9 vs. 63.5%, respectively; P < 0.001) in the non‐TA group compared with the ZDV group. As expected, the mutation K65R was found only in the non‐TA group (18.5%; P < 0.001). Conclusions At first‐line regimen failure, a lower prevalence of RTI resistance was found in patients treated with NNRTI + non‐TA compared with those treated with NNRTI + zidovudine + lamivudine. These results confirm that the choice of backbone may influence the prevalence of drug resistance at virological failure.